Role of tool size in suppressing defects in SPIF process - Hussain, Ghulam; Hashemipour, Majid; Iqbal, Asif; Khalatbari, Hosein (My University, 2013)
In the present work, the role of tool radius in suppressing forming defects in SPIF process is investigated. It is shown that a strong correlation exits between tool size and defect appearance. Moreover, there is a certain limit on choosing low limit of tool size for defect-free forming. A formula has been proposed to asses this limit under varied forming conditions. © (2013) Trans Tech Publications, Switzerland.
2013 Asian Pacific Conference on Chemical, Material and Metallurgical Engineering, APCCMME 2013 --
Keywords: Defect; Process parameter; SPIF; Tool size